Conversion of Waste from a Forest Products Mill to Biofuels - Anderson, Cody (My University, 2013)
Currently forest product mills across the country are producing large amounts of waste streams. In many of these plants these waste streams are simply being burned to produce electricity. Nevertheless, there are clearly other potential uses holding potentially higher value. The purpose of the research conducted was to explore two alternative methods for using two different biomass waste streams (Softwood and Hardwood). The two methods explored included a.) biofuels production through the conversion of sugars to ethanol and b.) the production of pyrolysis oil.